(untitled) - Shier, David (New York, NY, 2019)
Assuming no prior science knowledge, this book supports main concepts with clinical applications, making them more relevant to students pursuing careers in the allied health field.
Keywords: Giải phẩu người,Sinh lý học người,Human anatomy,Human physiology